2007
DOI: 10.2533/chimia.2007.100
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the Test-Tube as a Means to Create Selective Biocatalysts

Abstract: The development of chiral catalysts for use in synthetic organic chemistry is traditionally associated with progress in asymmetric transition metal catalysis or organocatalysis. In addition to these options chemists have employed enzymes for a number of asymmetric transformations for a long time. However, limited substrate acceptance and insufficient enantioselectivity are the crucial factors which prevent the general exploitation of biocatalysis in organic chemistry. In order to solve this long-standing probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The values of the X-ray structural parameters obtained for 3 AE 2C 6 H 5 CH 3 in our study are close to those for 3 reported in [8]. For other complexes containing C 5 H 4 BX 2 and C 5 H 4 B(C 6 F 5 ) 2 ligands, see, e.g., [32][33][34][35].…”
Section: Resultssupporting
confidence: 82%
“…The values of the X-ray structural parameters obtained for 3 AE 2C 6 H 5 CH 3 in our study are close to those for 3 reported in [8]. For other complexes containing C 5 H 4 BX 2 and C 5 H 4 B(C 6 F 5 ) 2 ligands, see, e.g., [32][33][34][35].…”
Section: Resultssupporting
confidence: 82%
“…In 1996, the Williams group reported the DKR of an allylic acetate derivative to produce the corresponding chiral alcohol by using PdCl 2 (MeCN) 2 and Pseudomonas fluorescens lipase. The DKR of amines was developed by the Reetz group, in which process the commercially available immobilized lipase Novozym435 catalyzed the resolution of 1‐phenylethylamine (1‐PEA) by stereoselective acylation whereas the Pd/C catalyzed the racemization of remaining ( S )‐phenylethylamine. Substantial efforts have been made to address the low efficiency of the combined enzymatic and metal catalysis process.…”
Section: Applications In Chemoenzymatic Cascade Reactionsmentioning
confidence: 99%
“…However, it is predicted that about 99 % of microorganisms are 'non-cultivable', and metagenomics -the extraction of environmental DNA -is proving highly successful in accessing novel biocatalysts from this untapped resource. 19 Further expansion in the number of commercially available enzymes and the modification of hits to suit process requirements is being fuelled by advances in enzyme engineering 20 and high-throughput screening (HTS) technologies. 21 A particularly elegant approach is the protein sequence activity relationship (ProSAR) technology developed by Codexis.…”
Section: Current Status Of Biocatalysismentioning
confidence: 99%